Comparison analysis of IoT based industrial automation and improvement of different processes – review. (2021) - Kamatchi Sundari, V.; Nithyashri, J.; Kuzhaloli, S.; Subburaj, Jayasudha; Vijayakumar, P.; Subha Hency Jose, P.
Abstract: In recent days, automation of process is playing an essential role in every industry. The quality, production rate and customer satisfaction are enhanced through automation process. The current situation every industry are facing problems such as process control and automation. The Internet of Things (IoT) has been introduced to solve the many industrial automation problems including metal to medical industries. The automation and improvement of different processes have been achieved through sensors, micro controller and LAN or wireless communications. This paper is focusing on IoT based automation and improvement of various process. A case study of performance of air quality has been studied.